The Reducing CO2 by Investing Solar Panel to Support Green Industry and Increasing Competitiveness Manufacturing Industry in Indonesia : - Yugo Prasetyo1; Selly Nissa Saputri (Universitas Pendidikan Ganesha, 2023)
Carbon dioxide emission (CO2) is one of the causes of climate change and global warming that affects air quality and threatens all creature’s lives. ASEAN countries have a big impact and Indonesia, as one of the ASEAN members, has a big contribution in increasing CO2 emission compared to other members, especially in the manufacturing industry sector. Indonesia has adapted the Green Industry and the Government supports renewable energy development and gives incentives such as tax allowance, tax holiday for large investment spur industrialization in Indonesia. Using solar panels is a manufacturer's strategy to fulfill demands and reduce the CO2 emission as targeted by the Government. This study is to examine the feasibility of the investment of solar panels to transform and adapt with climate change and to contribute to reducing the CO2 emission, increasing competitiveness in the manufacturing sector.